2021
DOI: 10.3390/en14206760
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Thornthwaite Moisture Index and Reactive Soil Movements under Current and Future Climate Scenarios—A Case Study

Abstract: Expansive soils go through significant volume changes due to seasonal moisture variations resulting in ground movements. The ground movement related problems are likely to worsen in the future due to climate change. It is important to understand and incorporate likely future changes in design to ensure the resilience of structures built on such soils. However, there has been a limited amount of work quantifying the effect of climate change on expansive soils movement and related behaviour of structures. The Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Soil slopes, i.e., cuttings or embankments, are an integral part of our transport network. Since the variability of material quality is common in soils, especially for silty or clayey soils (Karim et al, 2011;Devkota et al, 2022;Karim et al, 2022), the uncertainty on the stability of these slopes is an inherent challenge (Griffiths, 1982;Huang et al, 2006;Gould et al, 2011;Kasama and Whittle, 2011;Karim et al, 2021). Further, the mechanics for slope stability analysis that involves the conventional limit state approach uses simplifications and approximations, which adds to the uncertainty of their design.…”
Section: Introductionmentioning
confidence: 99%
“…Soil slopes, i.e., cuttings or embankments, are an integral part of our transport network. Since the variability of material quality is common in soils, especially for silty or clayey soils (Karim et al, 2011;Devkota et al, 2022;Karim et al, 2022), the uncertainty on the stability of these slopes is an inherent challenge (Griffiths, 1982;Huang et al, 2006;Gould et al, 2011;Kasama and Whittle, 2011;Karim et al, 2021). Further, the mechanics for slope stability analysis that involves the conventional limit state approach uses simplifications and approximations, which adds to the uncertainty of their design.…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell [28] showed that it is possible to account for expansive soil movement in design using empirical methods without heavily relying on experience. Later works [1,[30][31][32][33][34] highlighted the importance of better understanding the influence of atmospheric boundary interaction and changes in climate on the behaviour of shallow-depth structures on/in expansive soils. Several previous works have related climate with depth of suction change, e.g., Hu et al [35], Davenport [36], Walsh et al [37] and Fityus et al [38] generated depth of suction change (H s ) databases for different areas of Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The climate in Australia and around the world will continue to change in the coming decades, leading to significant socio-economic impacts [11]. Accounting for all climate variables can be a complex exercise, and changes in rainfall and temperature have been considered as the primary variables in most studies that investigated the soil-atmospheric boundary interaction, especially the ones looking at the effect of climate change [12][13][14][15][16][17]. Changes in temperature and rainfall may affect the behaviour of geotechnical infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the geolocation, local climate, expected future changes in the climate, and structure type, these effects can vary. Although soil-atmospheric boundary interactions have been an active area of research over the last two decades, limited attention has been paid to reactive soil movement and its interaction with structures [16]. This problem is likely to worsen because of climate change.…”
Section: Introductionmentioning
confidence: 99%